2009
DOI: 10.2134/jeq2008.0499
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Selenium Contamination in the Irrigated Stream–Aquifer System of the Arkansas River, Colorado

Abstract: Prudent interventions for reducing selenium (Se) in groundwater and streams within an irrigated river valley must be guided by a sound understanding of current field conditions. An emerging picture of the nature of Se contamination within the Lower Arkansas River Valley in Colorado is provided by data from a large number of groundwater and surface water sampling locations within two study regions along the river. Measurements show that dissolved Se concentrations in the river are about double the current Color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…However, these reduction reactions are inhibited in the presence of oxygen or nitrate (Zhang and Moore, 1997). Studies have reported that SeO 4 2− accounts for more than 90% of soluble Se in oxygenated waters (Gates et al, 2009;Gerla et al, 2011). In surface mining areas Se often exists at concentrations in excess of biological needs (Lindberg et al, 2011).…”
Section: How Does Mining Practice Affect Se Loading?mentioning
confidence: 99%
“…However, these reduction reactions are inhibited in the presence of oxygen or nitrate (Zhang and Moore, 1997). Studies have reported that SeO 4 2− accounts for more than 90% of soluble Se in oxygenated waters (Gates et al, 2009;Gerla et al, 2011). In surface mining areas Se often exists at concentrations in excess of biological needs (Lindberg et al, 2011).…”
Section: How Does Mining Practice Affect Se Loading?mentioning
confidence: 99%
“…In addition, overfertilization on cultivated fields has results in elevated groundwater C NO 3 , assessed by samples from 52 observation wells and 15 surface water sites (Arkansas River and tributaries) from 10 sampling events between 2006 and 2009 (Gates et al, 2009). In summary, the mean C NO 3 −N for the samples gathered from the 10 surface water sites along the Arkansas River was 1.53 mg/L and the mean for the samples from tributaries was 1.95 mg/L, as compared to the Colorado interim standard of 2 mg/L (CDPHE, 2012) for total N concentration C NO 3 −N þ À C NO 2 −N þ C NH 4 −N Þ in warm rivers and streams.…”
Section: Study Areamentioning
confidence: 99%
“…Similar to the forcing terms in the flow model regime, values were assigned only during the irrigation months of April through October, and were spatially-and temporally-variable, with each cell receiving a unique value differing from every other cell, with new values generated for each week of the irrigation season. Values of C s NO 3 for deep percolation water were selected randomly from a normal distribution with a mean equal to 25.0 g m À3 , corresponding to the mean of C NO 3 measured in a regional assessment of groundwater solutes in the LARV (Gates et al, 2009), and a mean of C s DOC equal to 20.0 g m f À3 based on samples of groundwater solutes in the LARV. Standard deviations for both distributions were set to 1.5, producing a spread of values (e.g., 17.0-33.0 g m À3 f for C s NO 3 ) large enough to take into account differences in N cycling (fertilizer application timing and loading, crop uptake, nitrification) in the root zone between locations, yet within the range expected from land management practices that are assumed to be fairly consistent in a spatial area of 4 km by 2 km.…”
Section: Conceptual Model Of Aquifer Systemmentioning
confidence: 99%
“…Standard deviations for both distributions were set to 1.5, producing a spread of values (e.g., 17.0-33.0 g m À3 f for C s NO 3 ) large enough to take into account differences in N cycling (fertilizer application timing and loading, crop uptake, nitrification) in the root zone between locations, yet within the range expected from land management practices that are assumed to be fairly consistent in a spatial area of 4 km by 2 km. The value of C s NO 3 for canal seepage water was set equal to 8.0 g m À3 f , typical for the LARV (Gates et al, 2009). …”
Section: Conceptual Model Of Aquifer Systemmentioning
confidence: 99%
See 1 more Smart Citation